2008
DOI: 10.1007/s00018-008-8346-1
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell therapy in stroke

Abstract: Recent work has focused on cell transplantation as a therapeutic option following ischemic stroke, based on animal studies showing that cells transplanted to the brain not only survive, but also lead to functional improvement. Neural degeneration after ischemia is not selective but involves different neuronal populations, as well as glial and endothelial cell types. In models of stroke, the principal mechanism by which any improvement has been observed, has been attributed to the release of trophic factors, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 128 publications
(139 reference statements)
2
82
0
Order By: Relevance
“…Among different transplantation routes, intravenous cell delivery has been used due to its simplicity and clinical practicability [8,25,26], although achieving low intracerebral cell numbers [15,27]. Therefore, local intracerebral injections are widely used, which can enhance the number of transplanted intracerebral cells but lack clinical utility due to invasive delivery procedures [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Among different transplantation routes, intravenous cell delivery has been used due to its simplicity and clinical practicability [8,25,26], although achieving low intracerebral cell numbers [15,27]. Therefore, local intracerebral injections are widely used, which can enhance the number of transplanted intracerebral cells but lack clinical utility due to invasive delivery procedures [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Infarct volume was ~25% smaller in the hES-MSC-recipient rats as determined by cresyl violet histological staining. Many other reports have produced similar results using MSC-like cells from multiple sources, including bone marrow-derived stromal cells, human umbilical cord blood stem cells, adipocyte-derived stem cells, as well as other types of stem cells, such as neural progenitor cells [see (Locatelli et al 2009) and (Bliss et al 2007) for reviews]. Chopp's group, in particular, has performed a large number of studies with rat, mouse or human MSCs in young, adult or aged animals and observed significant improvement in neurological function following stroke (Li & Chopp 2009).…”
Section: Hes-msc Transplantation Reduces Infarct Size and Improves Bementioning
confidence: 88%
“…To date, however, just a handful of small scale Phase I and Phase II clinical trials (summarized in Locatelli et al 2009) have been performed to test the safety of stem cell transplantation (of any type) in stroke patients, and of these, only one study used MSCs. This randomized Phase I/II study (Bang et al 2005) consisted of 30 patients with cerebral infarcts within the middle cerebral artery territory (as assessed by diffusion-weighted MRI) and severe neurological deficits (e.g., hemiparesis and agnosia; NIH Stroke Scale score of 7 or higher at 7 days after admission).…”
Section: Mscs In Clinical Trialsmentioning
confidence: 99%
“…Various human stem cells and their derivatives can differentiate into neurons restoring functional losses in the rodent stroke model [60,61] . In particular, human ESCderived NSCs, injected into the ischemic penumbra region in rat brains with ischemic stroke, have been reported to infarction area, and showed recovery of motor function [18] .…”
Section: Ischemic Strokementioning
confidence: 99%
“…move to the lesions, and improve motor performances [62] . Moreover, human adult temporal lobe-derived NSCs, grafted into the contralateral ventricle of the rat brains with focal cerebral stroke, significantly reduced the Initial clinical trials with stem cells have been completed in stroke [61] . Unfortunately, no significant clinical outcomes were observed when autologous MSCs were injected intravenously into ischemic patients [65] .…”
Section: Ischemic Strokementioning
confidence: 99%